Stamprofiler : en jämförelse mellan två olika apteringslistor - Grahn, Mikael (SLU/Dept. of Forest Products, 2006)
This report is a thesis work for a B.Sc. in Forestry at the 5028, SLU. The aim of the work was to compare two different pricelists with the actual output from a harvester. The results have also been compared with a volume estimate of standing trees done by the Swedish Forest Agency and the "true" value registered by the Wood Measurement Association.